Pseudo bilateral tonsilloliths: a case report and review of the literature - Ram, S.; Siar, C.H.; Ismail, S.M.; Prepageran, N.; Lumpur, K. (2004)
Tonsilloliths are very rare concretions found in the tonsillar crypt. They are usually single and unilateral, but occasionally may be multiple or bilateral. Small concretions in the tonsils are common, but well formed giant unilateral or bilateral tonsilloliths are extremely uncommon. Only two cases of bilateral tonsilloliths have so far been reported in the literature. A case of unilateral tonsillolith, mimicking bilateral tonsilloliths taken with the orthopantogram (OPT) in a 57-year-old Malaysian Indian female with squamous cell carcinoma of the oral cavity is described. Although the OPT is a reliable and standard panoramic X-ray unit used in dentistry, superimposition of a lesion involving one side of the jaw creates a pseudo or ghost image on the contralateral side leading to a misdiagnosis of bilateral lesions. This report highlights that tonsilloliths, though rare, should be considered in the differential diagnosis of radiopaque masses involving the mandibular ramus, and that investigations such as CT scan or MRI may be required to differentiate pseudo or ghost images from true bilateral pathologies.